The effect of eight weeks of high-intensity interval training with L-cysteine consumption on interleukin-13 and oxidative stress of heart tissue in young rats with type 2 diabetes - Mana Davoudi; Akbar Nouri Habashi (Journal of Shahrekord University of Medical Sciences, 2023)
Background and aims: The purpose of this study was to investigate the effect of 8-weeks of high-intensity interval exercise with L-cysteine (LC) consumption on interleukin (IL)-13 and hydrogen peroxide of the heart tissue in young rats with type 2 diabetes (T2D). Methods: The statistical population of the present study consisted of young (4-month) rats with T2D. Ten rats were selected as a healthy group. Forty rats became diabetic. Diabetic rats were randomly divided into diabetes control, diabetics with exercise, diabetics with supplements, and diabetics with exercise and supplements. High-intensity interval exercises were performed 3 days a week for 8 weeks, and 500 μmol of LC were injected daily. Results: The healthy control group had lower IL-13 than the control group (P=0.001). There was no significant difference in IL-13 between other groups. Based on the results, the diabetes control group had a higher H2 O2 value than the healthy control group (P=0.001). A significant difference was found between the exercise group+LC consumption compared to the diabetes control group, and the H2 O2 levels in this group were less than the diabetic control group (P=0.001). The exercise (P=0.015) and LC (P=0.001) groups had a lower H2 O2 value than the diabetes control group. Eventually, the interval exercise group+LC was also lower than the periodic exercise group (P=0.02). Conclusion: High-intensity interval training, along with the use of LC, reduced hydrogen peroxide in the heart tissue, while it had no significant impact on IL-13.